2014
DOI: 10.1542/peds.2013-3392
|View full text |Cite
|
Sign up to set email alerts
|

Thirdhand Smoke Beliefs of Parents

Abstract: Thirdhand smoke harm belief was associated with a strictly enforced smoke-free home and car and attempts to quit smoking. Sensitizing parents to thirdhand smoke risk could facilitate beneficial tobacco control outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 22 publications
1
34
0
2
Order By: Relevance
“…THS health impact items were used to ask about general health impact of THS on children [6, 11, 17] and adults [4, 23] as well as cancer specifically [24, 25] with three items. Three items pertaining to THS persistence included days, weeks, and months separately [7, 20]. Three additional items with statements about smoke particles settling with dust [11], accumulating on surfaces [4] and being absorbed into furniture and walls [8] aimed at THS accumulation in the built environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…THS health impact items were used to ask about general health impact of THS on children [6, 11, 17] and adults [4, 23] as well as cancer specifically [24, 25] with three items. Three items pertaining to THS persistence included days, weeks, and months separately [7, 20]. Three additional items with statements about smoke particles settling with dust [11], accumulating on surfaces [4] and being absorbed into furniture and walls [8] aimed at THS accumulation in the built environment.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, education about THS has been incorporated into interventions to promote home smoking bans [18, 19]. Drehmer [20] found that THS harm beliefs were related to more strict enforcement of smoke free bans in homes and cars and increased numbers of quit attempts, which is encouraging evidence for inclusion of THS education in interventions aiming to decrease the impact of tobacco use [21]. Based on this literature, more accurate knowledge and beliefs about THS might be associated with being a nonsmoker, having a smoke-free home, and having been exposed to education regarding the harms of THS.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Better parental health education regarding the harms to children' s health due to exposure to secondhand smoke and third-hand smoke could help motivate more parents to quit smoking. 30 We also found that parents who reported Excluded all the parents who did not have a visit to their child' s pediatric office in the last 12 mo; N = 1191. SHS, secondhand smoke.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, parents who reported receiving advice during their pediatrician visit regarding quitting smoking or maintaining a smoke-free home or car were more likely to endorse the belief that THS is harmful to children and infants. Believing that THS is harmful was also associated with making at least one quit attempt (Drehmer et al, 2014). …”
Section: Thirdhand Smoke Beliefs and Behaviors Among Healthcare Profementioning
confidence: 99%